A SOCIOLINGUISTICS STUDY OF SLANG WORDS USED BY HOMELESS DRIFTER IN SALATIGA - MAHARANI , TANTINI (2007)
This research paper is about the slang words used by homeless drifter in Salatiga. The objectives of the research are to find the forms of slang words and to show the meaning of the slang words. The data of slang words used by homeless drifter in Salatiga are in the forms of words, abbreviation, differentiate structural, numbered and code. In collecting the data, the writer uses observation, note taking and interview method. Further more, in analyzing the data, the writer clarifies the forms of slang words and employs the sociolinguistics theory. The result of the data analysis shows that (1) there are four forms of slang words used by Homeless drifter in Salatiga, namely: the part of speech consist of noun (N), verb (V), adverb (Adv), and adjective (Adj), (2) There are four kinds of the meanings of the slang words used by Homeless drifter in Salatiga that is abbreviation, formed by differentiating structure, number and code